WCSdb: a database of wild Coffea species. (20th November 2020) - Guyot, Romain; Hamon, Perla; Couturon, Emmanuel; Raharimalala, Nathalie; Rakotomalala, Jean-Jacques; Lakkanna, Sreenath; Sabatier, Sylvie; Affouard, Antoine; Bonnet, Pierre
Abstract: Coffee is a beverage enjoyed by millions of people worldwide and an important commodity for millions of people. Beside the two cultivated species ( Coffea arabica and Coffea canephora ), the 139 wild coffee species/taxa belonging to the Coffea genus are largely unknown to coffee scientists and breeders although these species may be crucial for future coffee crop development to face climate changes. Here we present the Wild Coffee Species database (WCSdb) hosted by Pl@ntNet platform (http://publish.plantnet-project.org/project/wildcofdb_en ), providing information for 141 coffee species/taxa, for which 84 contain a photo gallery and 82 contain sequencing data (genotyping-by-sequencing, chloroplast or whole genome sequences). The objective of this database is to better understand and characterize the species (identification, morphology, biochemical compounds, genetic diversity and sequence data) in order to better protect and promote them. Database URL: http://publish.plantnet-project.org/project/wildcofdb_en